THE EFFECT OF RENEWABLE ENERGY CONSUMPTION AND ENERGY INTENSITY ON THE ECONOMY - Nurlaila Indah Sari; Toto Gunarto; Neli Aida (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of Renewable Energy Consumption and Energy Intensity on the economy in ASEAN. The variables used in this study consisted of Renewable Energy Consumption (REC), Energy Intensity (EI), and Gross Fixed Capital Formation (GFCF). This research method uses panel data regression analysis with the Random Effect Model. Where cross-sectional data are 7 ASEAN member countries and time series data from 2010-2021. The results of the study show that all variables, namely REC, EI and GFCF, are all significant to GDP. REC with a coefficient of -6,921,893 and a significance of 0.0000 < 0.05 so that REC has a negative impact on GDP in ASEAN. EI has a coefficient of -76,701.51 and a significance of 0.0000 < 0.05 so that EI has a negative impact on GDP. Meanwhile, GFCF has a coefficient of 91,930.69 and a significance of 0.0000 < 0.05 so that GFCF has a positive impact on GDP. The R2 value of 0.6083 can be concluded that the variation of these independent variables contributes 60.83 percent in GDP. While the rest are influenced by other factors that are not described in the model.